Veterinary fluoroquinolones as emerging contaminants in marine environments: In vitro study of biochemical responses in subcellular fractions of the Mediterranean mussel (Mytilus galloprovincialis) - J. Giannessi; L. De Marchi; V. Meucci; L. Intorre; G. Monni; M. Baratti; C. Pretti (Heliyon)
Fluoroquinolone antibiotics (FQs) are emerging pollutants frequently detected in aquatic environments. However, their impact on marine invertebrates remains underexplored. This study investigated the responses at subcellular level in the Mediterranean mussel (Mytilus galloprovincialis) exposed to three veterinary FQs, marbofloxacin (MARB), sarafloxacin (SARA), and difloxacin (DI), at concentrations considered relevant to environmental conditions. The assessment focused on the digestive gland and gills, employing in vitro assays to evaluate antioxidant defenses, biotransformation, and neurotransmission enzyme activities, as well as their effects on membrane lipids, proteins, and DNA integrity. Results revealed a general decline in antioxidant defenses and compromised DNA integrity in both tissues. Additionally, exposure to MARB and DI led to an alteration in detoxification capacity in the gills, along with an increased content of carbonylated proteins. Conversely, the digestive gland exhibited a significant inhibition of acetylcholinesterase activity. These findings suggest potential neurotoxic and genotoxic impacts of these antibiotics on non-target species, as well as an associated oxidative effect.